Youth Voices and Social Participation during a Pandemic: Dream Teens Powered by Jovem Cascais - Cátia Branquinho; Sara Silva; Joana Santos; Inês Sousa Martins; Catarina Gonçalves; Catarina Noronha; Tânia Gaspar; Margarida Gaspar de Matos (Youth, 2022)
In an unprecedented scenario, much of the research and interventions during the COVID-19 pandemic, which focused on young people, found themselves suspended. (1) Background: The goals of this project were to investigate (Study 1) social participation and positive development among young people in Cascais, Portugal, and to investigate (Study 2-a case study) the implementation of a program promoting active citizenship, social participation, and social entrepreneurship. At the same time, it was intended to constitute a resource and strategy to diminish the social alienation exacerbated by the pandemic. (2) Methods: SPSS v.26 software was used to analyze quantitative data from questionnaires used in the study of social participation, as well as the pre- and post-test impacts, and MAXQDA 2020 software was used to analyze qualitative data from YouTube discussions about youth needs and strategies for their problems, as well as from focus groups. (3) Results: In S1, it was evident that young people’s expectations of participation in the community were not defined and that their expected participation in the community was of a weekly nature. They considered themselves to have a good sense of belonging to the community or group and had reasonable social self-efficacy. Girls showed higher scores in Expectations of Community Participation and Active Participation. In their positive development, they did not have a defined evaluation of their competence, but their connection with others was evaluated as good. Boys showed higher levels of Competence. They said that every week they make 1 h of their day available to help others, and they did not frequently report feelings of social alienation. In S2, the evaluation of the impact of the project generally showed an improvement in the action research skills of the participants. At the end, six projects were proposed. In the analysis of the participants’ voices, the themes related to Substance Use, Social Capital, and Love and Sexuality stood out with higher participation and lower participation in the themes of Diversity, Culture and Housing. (4) Conclusions: The results suggest a need to encourage social participation, active citizenship, and entrepreneurship, along with their knowledge and skills for action. The promotion of debate and knowledge on issues related to young people’s lives seems to be a priority, especially issues related to Diversity, Culture and Housing. The Dream Teens model may prove to be an important strategy in this work, suggesting that this project may constitute a relevant model for future work.